Establishment of an experimental model of ovalbumin-induced atopic dermatitis in canines - Shin, Ha-Young; Jin, Hyung Jun; Tae, Hyun-Jin; Oh, Hong-Geun; Hwang, Jeong Ho (Frontiers in Veterinary Science, 2024)
A reliable standard model is required to evaluate the efficacy of new drugs for companion animals, especially dogs. Canine atopic dermatitis (cAD), also known as allergic inflammatory skin disease, is a common condition. Currently, the house dust mite animal model is used in the research of cAD; however, this model exhibits significant individual variation and is difficult to standardize. In this study, we used ovalbumin as an antigen to sensitize and stimulate dogs, thereby establishing a stable model mimicking the T-helper 2 (Th2) response seen in cAD. Our objective was to create a cAD model that could be employed to evaluate the efficacy of novel drugs and mimic the Th2 dominant allergic response observed in the pathogenesis of atopic dermatitis of dogs. In this study, six beagles were used. Normal saline was applied to two animals, and ovalbumin to four, on their dorsal skin. The ovalbumin-treated groups exhibited clinical cAD symptoms, such as pruritus and erythema. Moreover, plasma levels of the cAD markers immunoglobulin E and CCL17 chemokine were higher in the ovalbumin-treated group than in the vehicle control group. The skin thickness of the epidermis was significantly increased in the ovalbumin-treated group, with infiltration of inflammatory cells observed in the thickened dermis region. In conclusion, treatment of canine skin with an optimal concentration of ovalbumin induced typical cAD-like symptoms, and histological and molecular analyses confirmed an enhanced Th2-related immune response. Therefore, we successfully established a suitable Th2-dominant response mimicking cAD, which will facilitate targeted research of atopic dermatitis in dogs.